Vascular injury associated with ethanol intake is driven by AT1 receptor and mitochondrial dysfunction - Awata, Wanessa M.C.; Alves, Juliano V.; Costa, Rafael M.; Bruder-Nascimento, Ariane; Singh, Shubhnita; Barbosa, Gabriela S. [UNESP]; Tirapelli, Carlos Renato; Bruder-Nascimento, Thiago (Elsevier, 2023)
Background: Renin-angiotensin (Ang II)-aldosterone system (RAAS) is crucial for the cardiovascular risk associated with excessive ethanol consumption. Disturbs in mitochondria have been implicated in multiple cardiovascular diseases. However, if mitochondria dysfunction contributes to ethanol-induced vascular dysfunction is still unknown. We investigated whether ethanol leads to vascular dysfunction via RAAS activation, mitochondria dysfunction, and mitochondrial reactive oxygen species (mtROS). Methods: Male C57/BL6J or mt-keima mice (6–8-weeks old) were treated with ethanol (20% vol./vol.) for 12 weeks with or without Losartan (10 mg/kg/day). Results: Ethanol induced aortic hypercontractility in an endothelium-dependent manner. PGC1α (a marker of biogenesis), Mfn2, (an essential protein for mitochondria fusion), as well as Pink-1 and Parkin (markers of mitophagy), were reduced in aortas from ethanol-treated mice. Disturb in mitophagy flux was further confirmed in arteries from mt-keima mice. Additionally, ethanol increased mtROS and reduced SOD2 expression. Strikingly, losartan prevented vascular hypercontractility, mitochondrial dysfunction, mtROS, and restored SOD2 expression. Both MnTMPyP (SOD2 mimetic) and CCCP (a mitochondrial uncoupler) reverted ethanol-induced vascular dysfunction. Moreover, L-NAME (NOS inhibitor) and EUK 134 (superoxide dismutase/catalase mimetic) did not affect vascular response in ethanol group, suggesting that ethanol reduces aortic nitric oxide (NO) and H2O2 bioavailability. These responses were prevented by losartan. Conclusion: AT1 receptor modulates ethanol-induced vascular hypercontractility by promoting mitochondrial dysfunction, mtROS, and reduction of NO and H2O2 bioavailability. Our findings shed a new light in our understanding of ethanol-induced vascular toxicity and open perspectives of new therapeutic approaches for patients with disorder associated with abusive ethanol drinking.
Keywords: Ethanol; Mitochondria; Reactive oxygen species; Vascular dysfunction